Thermoregulatory reactions of female buffaloes raised in the sun and in the shade, in the climatic conditions of the rainy season of the Island of Marajó, Pará, Brazil - Silva, Jamile Andréa Rodrigues da; Pantoja, Messy Hennear de Andrade; Silva, Welligton Conceição da; Almeida, Jean Caio Figueiredo de; Noronha, Rafaella de Paula Pacheco; Barbosa, Antônio Vinicius Corrêa; Lourenço Júnior, José de Brito (Frontiers in Veterinary Science, 2022)
Buffaloes are well-adapted to hot, humid climates and muddy terrain, however they show signs of thermal discomfort when exposed to direct sunlight due to their specific structural features such as dark skin, small number of sweat glands/skin area and thick skin. Epidermis layer of the skin, making heat dissipation difficult. The study aimed to evaluate the thermal comfort of female buffaloes raised in traditional and silvopastoral systems, on the island of Marajó, Pará, during the rainy season of the year. The experiment was carried out in Cachoeira do Arari, Retiro Grande, Marajó, Pará (00°55'37.814424”S 48°43'48.143060”W). Twenty female Murrah buffaloes, aged between 2 and 3years and average weight of 282 ± 29 kg, were used. They were fed on pasture and divided into two groups: WS group (with shade) and NS group (without shade). The WS group (n = 10) remained grazing in a silvopastoral system, with access to the shade of red Jambeiro (Syzygium malaccense) trees. The NS group (n = 10) was kept in grazing, in a traditional system, without access to the shade of trees or shades. The physiological variables rectal temperature (RT), respiratory rate (RR) and body surface temperature (BST) (forehead, left side of the thorax and left flank) were measured at 6:00, 10:00, 14:00, 18:00, and 22:00 h. At the same times, data on air temperature, relative air humidity, wind speed (WSP), solar radiation (SR) and Temperature and Humidity Index (THI) were also recorded. THI, WSP and SR were higher at 14:00 h (P < 0.05). At 10:00, 14:00, and 18:00 h there was difference of RT between treatments (P < 0.05), where animals of the NS group had the highest values. In the NS group, the highest value of RT was observed at 14:00 h (39.38 ± 0.43°C), when THI and SR were higher. At 10:00 and 14:00 h, BST was higher in the NS group (p < 0.05), of 34,55 ± 1.03 and 35.35 ± 1.51°C, respectively, and both groups had the highest value of BST at those same times. There was difference of the RR between treatments at 10:00 h and 14:00 h (p < 0.05), where the highest values were found in the NS group (33.71 ± 7.58 e 50.40 ± 18.41 mov./min., respectively). Even in the rainy season of the year, the climatic conditions of Ilha do Marajó are unfavorable to the welfare of buffaloes, especially at 2:00 pm, when the SR is higher. Thus, the use of the system with access to shade, such as silvopastoral, is recommended, in order to provide greater thermal comfort to animals and improve their productivity.